Discussions and Conclusions - Smits, Joris (A+BE | Architecture and the Built Environment, 2019)
In the previous four chapters design considerations for bridges have been identified at the four principal scale levels of the design; the scale of the landscape and the city, the scale of the bridge itself, the scale of the detail and at the scale of the composing material and the material properties. This chapter provides an integrated discussion and conclusions on the broad field of bridge design as it is outlined in the main body of this dissertation. The following chapter, Chapter 7, presents the recommendations for future research.